A READING PROGRAMME FOR STUDENTS - Suhaimi, Suhaimi (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri (IAIN) Kerinci, 2016)
This article explores reading programs that used by students in learning English System, Inc, and students attitudes towards reading while specifically focusing on the difference in attitudes toward reading between low achieving and high achieving students. In addition, this article describes the reading achievement and the use of the Reader Program.